Sold - McCormick, Patricia, 1956- (Hyperion, 2006)
Thirteen-year-old Lakshmi leaves her poor mountain home in Nepal thinking that she is to work in the city as a maid only to find that she has been sold into the sex slave trade in India and that there is no hope of escape.